Using Large Scale Individual Creativity to Improve Organisational Efficiency - Clapp, PhD, Ray; Rucktum, PhD, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2016)
Abstract This study reviews the outcomes from six similar organisational interventions two from the USA, three from the UK (one using Appreciative Inquiry) and one from Romania. By way of an illustration the process used by one of the interventions (Clapp, 1991) is described in detail. This process uses a well-defined problem to elicit potential solutions from people working in the organisation who have knowledge of the problem area. The results are compared with the five other interventions that use a similar process. The results show that given a supportive environment and a clear objective most people will engage in a problem-solving exercise and generate many ideas, the bulk of which are set within the current context. The number of ideas generated per person ranged between 1.33 and 1.53. Whereas for the project that used Appreciative Inquiry the number of ideas generated per person was 2.3. The average value of the savings from the ideas of each project ranged between £3.44K and £6.88K. These studies provide support for the theory that all people are creative problem-solvers given the opportunity to become active participants (Kirton 2003). Furthermore, to make use of this creativity in an organisation, managers have to provide a setting that will support and motivate individuals to focus their potential on a target of organisational importance. Key Words: Individual Creativity, Organisational Performance, OD Process Replication.